2015
DOI: 10.1002/polb.23706
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the self-assembly of poly-(3-hexylthiophene) using solubility and solvatochromic parameters

Abstract: The assembly of poly(3-hextylthiophene) (P3HT) in solvent mixtures is studied using solubility and solvatochromic parameters. Correlations between the excitonic coupling of P3HT assemblies and the Kamlet-Taft (a, b, p*) and E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…The CF:DCM and CF:AcN blends were primarily chosen because of significant differences in the assembly behavior and the characteristics of the P3HT aggregate phase in these mixtures. Specifically, P3HT assembles into disordered H ‐type aggregates in all of the CF:AcN mixtures we have studied, but in CF:DCM we observe a range of highly ordered (crystalline) J ‐type aggregates and H ‐type aggregates depending on the volume fraction of DCM in the solvent blend . In a previous paper in this journal we stressed that an additional advantage of using these solvent mixtures is that they generate larger amounts of P3HT aggregates compared to aggregate growth in pure marginal solvents, which may help circumvent one of the proposed weaknesses of the chemical doping methodology .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The CF:DCM and CF:AcN blends were primarily chosen because of significant differences in the assembly behavior and the characteristics of the P3HT aggregate phase in these mixtures. Specifically, P3HT assembles into disordered H ‐type aggregates in all of the CF:AcN mixtures we have studied, but in CF:DCM we observe a range of highly ordered (crystalline) J ‐type aggregates and H ‐type aggregates depending on the volume fraction of DCM in the solvent blend . In a previous paper in this journal we stressed that an additional advantage of using these solvent mixtures is that they generate larger amounts of P3HT aggregates compared to aggregate growth in pure marginal solvents, which may help circumvent one of the proposed weaknesses of the chemical doping methodology .…”
Section: Introductionmentioning
confidence: 79%
“…To our knowledge there are few, if any, reports which systematically investigate the behavior of F4TCNQ‐doped P3HT in the liquid phase using binary solvent mixtures. The study reported herein, which expands on our earlier work, is a preliminary investigation of the behavior of F4TCNQ‐doped P3HT in binary solvent mixtures composed of chloroform (CF) with dichloromethane (DCM) or acetonitrile (AcN). The CF:DCM and CF:AcN blends were primarily chosen because of significant differences in the assembly behavior and the characteristics of the P3HT aggregate phase in these mixtures.…”
Section: Introductionmentioning
confidence: 85%
“…Indeed, research going as far back as 20 years has questioned this hypothesis of symmetry. 3 A recent report on the solvent-induced recrystallization of poly(3-hexylthiophene) (P3HT) provides evidence that variations in the three solubility parameters do not equally impact the behavior of P3HT; 21 thus, for P3HT, a solubility region exhibiting a complex volume appears valid.…”
Section: 33mentioning
confidence: 99%
“…3,[6][7][8][9][10][11][12][13] Additionally, there has been significant interest in using solubility parameters to investigate the effect of solvent-polymer interactions on the morphology, crystallinity, and performance of functional polymeric materials. [14][15][16][17][18][19][20][21] Despite the well-established and widely used framework of solubility parameter methods, the literature is frequently updated with studies that continue to validate, challenge, and refine their principles and practices.…”
mentioning
confidence: 99%
“…Recently, the development of techniques to reliably tune the BHJ morphology by altering the nature of the donor and acceptor interactions with the solvent(s) used to process the thin film composites has attracted a lot of attention. As a consequence of these endeavors, there is a renewed interest in solubility parameters and their application to polymeric materials …”
Section: Introductionmentioning
confidence: 99%